THE EFFECT OF ASTA BRATA LEADERSHIP ON JOB SATISFACTION IN VILLAGE CREDIT INSTITUTIONS (LPD) IN TABANAN REGENCY - Ngurah Made Novianha Pynatih; I Putu Gelgel; I Nengah Lestawi (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2022)
Village credit institutions or known as LPDs are microfinance institutions that have a very important position in traditional villages. Village credit institutions have the authority to implement their management based on the respective traditional village pararem. Given the important position of village credit institutions in improving the welfare of local communities, village credit institutions must be improved as a financial institution. Given the number of problematic village credit institutions in Tabanan Regency caused by many mismanagement of the leadership, this study was conducted to see the influence of Asta Brata's leadership on employee satisfaction at village credit institutions (LPD) in Tabanan Regency. This study used a sample of 93 people from a total population of 1190 people. Sampling using the Proportionate Stratified Random Sampling method. The data analysis technique uses path analysis. Collecting information from respondents using a questionnaire with a Likert scale. Data from respondents is still in ordinal scale units and the data processing requirements used are path analysis, so the data must be increased to intervals using the interval successive method.The results of this study are to answer the proposed hypothesis. The results showed that the leadership of Asta Brata with subvariables Indra Brata, Yama Brata, Surya Brata, Candra Brata, Bayu Brata, Kuwera Brata, Baruna Brata and Agni Brata had a positive and significant effect on employee job satisfaction at village credit institutions in Tabanan Regency. Asta Brata with the greatest influence on job satisfaction at village credit institutions (LPD) in Tabanan Regency is Indra Brata. If you want to increase job satisfaction in village credit institutions (LPD) in Tabanan Regency, you need to improve Indra Brata's leadership first and then the others.